ANATOMICAL STRUCTURE AND FUNCTIONS OF THE KIDNEY. NEPHRON. (Journal of Universal Science Research, 2023)
This article provides a detailed understanding of kidney anatomy, nephron anatomy. Information about the processes performed by the kidney, as well as its responsibility for the reabsorption of water, glucose and amino acids, and the maintenance of the balance of these molecules in the body. In addition, the kidneys produce hormones, including calcitriol, erythropoietin, and the enzyme renin, which are involved in renal and hematologic physiological processes.